Digitalization and Leap Frogging Strategy Among the Supply Chain Member: Facing GIG Economy and Why Should Logistics Players Care? - Abdul Rahman, Nor Aida; Muda, Jailani; Mohammad, Mohammad Fakhrulnizam; Ahmad, Md Fauzi; Abdul Rahim, Suzari; Mayor-Vitoria, Fernando (International Journal of Supply Chain Management, 2019)
This article integrates the concept of leap frogging strategy and digitalization as a key strategy for the sustainability of logistics players in facing up with GIG economy. At present, business organization are moving towards Industry 5.0 (internet of thought) and GIG economy where the traditional way of fully relying on full time workers are no longer relevant. The world of work is changing. From organizational view, leap frogging strategy with technological advancement are significant to achieve competitive advantage to ensure the continuity of business. While from worker perspective, having technology driven talent is a must to face new business economy called as GIG economy. In other words, all workers in every industry including logistics should ensure they have technology driven talent in his/her portfolio to remain competitive in the working world. Therefore, the aim of this study is to explore the applicability of Industry 5.0 such as digitalization and mobile marketing to logistics players; to make them more visible to customer and competitor. Single case study method was adopted to study on the perspective as discussed above more in-depth. Findings from this single case study is transferable as it provides rich explanation and discussion from one of the earliest logistics company in Malaysia, with logistics experience almost five (5) decades in providing logistics services. The qualitative findings pointed out four key areas for LSP improvement. Firstly, all LSPs should go for transition process with their business model to provide them with new revenue - logistics digital business and allow them to be more visible to their customer by fully utilizing the promotion activities online. Secondly, every agreement with customer should be put into contract and it is paperless within system. Thirdly, digital payment is a must to all logistics players to practice in order for them to compete in digital era. Finally, and inevitability, to sustain in the business, logistics may move to become intelligent logistics players with carrying no asset and just focus on negotiating contracts with customers. This term refers to practising logistics players with no assets or less assets centric. In principle, the company does not own asset but able to provide logistics services (for example fleet and warehouses) by aggregating â€œinformation about assetsâ€ from people who do own them by leveraging on data. This article contributes to the logistics study by matching issue on digitalization and GIG economy in logistics sector. More work on future of logistics is needed with large sample across the globe in order to obtain more data to help the logistics players depict themselves in new economy.